Insulin Therapy in Type 2 Diabetes Is Associated With Barriers to Activity and Worse Health Status: A Cross-Sectional Study in Primary Care - Boels, Anne Meike; Rutten, Guy; Cleveringa, Frits; van Avendonk, Mariëlle; Vos, Rimke (Frontiers in Endocrinology, 2021)
Introduction: Many individuals with type 2 diabetes mellitus (T2DM) experience ‘psychological insulin resistance’. Consequently, it could be expected that insulin therapy may have negative effects on psychological outcomes and well-being. Therefore, this study compared health status and psychosocial functioning of individuals with T2DM using only oral antihyperglycemic agents (OHA) and on insulin therapy (with or without OHA). Materials and Methods: In this cross-sectional study we used baseline data of a cluster randomized controlled trial conducted in 55 Dutch general practices. Health status was measured with the Short Form (SF)-36 (scale 0-100) and psychosocial functioning with the Diabetes Health Profile (DHP, scale 0-100). To handle missing data, we performed multiple imputation. We used linear mixed models with random intercepts per general practice to correct for clustering at practice level and to control for confounding. Results: In total, 2794 participants were included in the analysis, their mean age was 65.8 years and 50.8% were women. Insulin-users (n = 212) had a longer duration of T2DM (11.0 versus 5.6 years) and more complications. After correcting for confounders and multiple comparisons, insulin-users reported significantly worse outcomes on vitality (SF-36, adjusted difference -5.7, p=0.033), general health (SF-36, adjusted difference -4.8, p=0.043), barriers to activity (DHP, adjusted difference -7.2, p<0.001), and psychological distress (DHP, adjusted difference -3.7, p=0.004), all on a 0-100 scale.